Mitigating and Preparing for Disasters at the Organizational Level: A Global Systematic Literature Review - Abdul-Akeem Sadiq; Ratna B. Dougherty; Rebecca Entress; Bikash Adhikari; Katherine Wilson McCoy; Emilie Rott; Grace L. Chikoto-Schultz; Shannon Maharajh (International Journal of Disaster Risk Science)
Abstract Organizations play significant roles in society by providing goods and services and contributing to the economies of communities, globally. Amid the predicted increase in the frequency and impact of disasters, which will invariably lead to higher disaster costs, there is an urgent need to ameliorate disaster impact on society and organizations. Disaster mitigation and preparedness are strategies for stemming disaster impact and losses within organizations. Cognizant of the importance of disaster mitigation and preparedness, researchers have conducted a myriad of studies on both concepts at the organizational level. To advance knowledge on this topic, this study conducted a comprehensive systematic literature review by examining the global trends in disaster mitigation and preparedness research at the organizational level, identifying research gaps in methodological dimensions, and recommending future research topics based on gaps in the literature. The authors searched three databases—Web of Science, EBSCO-ProQuest, and ABIinform—for keywords related to the topic and conducted a reverse citation search of the identified studies from the initial search, resulting in a final list of 123 studies. The findings indicate that research on this topic is relatively young and tends to mostly occur in collaborative environments. Additionally, most studies are quantitative and empirical in nature, and much of the research is on North America and Asia. Furthermore, while three-quarters of the studies do not specify a particular hazard type, among those that do, most focus on earthquakes and terrorist attacks in Asia and North America respectively, among other hazard types. This study concluded by recommending areas for future research.